2014
DOI: 10.1002/casp.2208
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Negative Images on Young People's Willingness to Help Elderly People

Abstract: We examined the effect of confronting young people with an image depicting them as unhelpful on their willingness to help elderly people. As expected, helpfulness increased when this image reflected the elderly's view of young people but decreased when it reflected objective information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Researchers have evoked metastereotypes by showing respondents an article (sometimes purported to have appeared online, van Leeuwen & Täuber, 2012, or in a newspaper, van Leeuwen & Jongh, 2015) that describes how a certain outgroup views the respondents’ ingroup. As in Van Leeuwen and Jongh (2015), we asked young adults to read an article describing how older adults viewed people aged 18 to 30 years. We explained that the article “summarizes some of the things that older adults think and believe about members of the millennial generation.” Each article used research (with hyperlinks provided) to highlight traits attributed to young adults.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have evoked metastereotypes by showing respondents an article (sometimes purported to have appeared online, van Leeuwen & Täuber, 2012, or in a newspaper, van Leeuwen & Jongh, 2015) that describes how a certain outgroup views the respondents’ ingroup. As in Van Leeuwen and Jongh (2015), we asked young adults to read an article describing how older adults viewed people aged 18 to 30 years. We explained that the article “summarizes some of the things that older adults think and believe about members of the millennial generation.” Each article used research (with hyperlinks provided) to highlight traits attributed to young adults.…”
Section: Methodsmentioning
confidence: 99%
“…However, recent studies have collated counter-evidence that they do care about their reputation even when interacting with out-group members (Romano et al, 2017;Yazdi et al, 2020). Moreover, several studies have found that individuals sometimes help out-group members so that the out-group has a positive image of their own group (e.g., Hopkins et al, 2007;van Leeuwen & Jongh, 2015). Thus, past studies suggest that it is important 23 has not been directly studied.…”
mentioning
confidence: 99%